Obstruction of the formation of granulation tissue leads to delayed wound healing after scald burn injury in mice. Issue 1 (29th April 2021) - Chen, Yunxia; Zhang, Xiaorong; Liu, Zhihui; Yang, Jiacai; Chen, Cheng; Wang, Jue; Yang, Zengjun; He, Lei; Xu, Pengcheng; Hu, Xiaohong; Luo, Gaoxing; He, Weifeng
Abstract: Background: Delayed wound healing remains a common but challenging problem in patients with acute or chronic wound following accidental scald burn injury. However, the systematic and detailed evaluation of the scald burn injury, including second-degree deep scald (SDDS) and third-degree scald (TDS), is still unclear. The present study aims to analyze the wound-healing speed, the formation of granulation tissue, and the healing quality after cutaneous damage. Methods: In order to assess SDDS and TDS, the models of SDDS and TDS were established using a scald instrument in C57BL/6 mice. Furthermore, an excisional wound was administered on the dorsal surface in mice (Cut group). The wound-healing rate was first analyzed at days 0, 3, 5, 7, 15 and 27, with the Cut group as a control. Then, on the full-thickness wounds, hematoxylin and eosin (H&E) staining, Masson staining, Sirius red staining, Victoria blue staining and immunohistochemistry were performed to examine re-epithelialization, the formation of granulation tissue, vascularization, inflammatory infiltration and the healing quality at different time points in the Cut, SDDS and TDS groups. Results: The presented data revealed that the wound-healing rate was higher in the Cut group, when compared with the SDDS and TDS groups. H&E staining showed that re-epithelialization, formation of granulation tissue and inflammatory infiltration were greater in the Cut group, when compared with the SDDS and TDS groups. Immunohistochemistry revealed that the number of CD31, vascular endothelial growth factor A, transforming growth factor-β and α-smooth muscle actin reached preferential peak in the Cut group, when compared with other groups. In addition, Masson staining, Sirius red staining, Victoria blue staining, Gordon-Sweets staining and stress analysis indicated that the ratio of collagen I to III, reticular fibers, failure stress, Young's modulus and failure length in the SDDS group were similar to those in the normal group, suggesting that healing quality was better in the SDDS group, when compared with the Cut and TDS groups. Conclusion: Overall, the investigators first administered a comprehensive analysis in the Cut, SDDS and TDS groups through in vivo experiments, which further proved that the obstacle of the formation of granulation tissue leads to delayed wound healing after scald burn injury in mice.